IAIN PADANGSIDIMPUAN STUDENTS' PERCEPTIONS OF INTERNET BANKING SERVICE SECURITY IN ISLAMIC BANKING TRANSACTIONS - riani ade; replita replita; arti damisa; damri batubara (Institut Agama Islam Negeri Padangsidimpuan, 2022)
Internet Banking service is one of the banking services that allows customers to obtain information, communicate, and perform banking transactions through the internet network. However, there are still a few who use or utilize internet banking services in transactions. This is due to the lack of customer knowledge about internet banking where there are still many customers who are still afraid to use this service for security reasons. Because technically, security refers to the existence of legal guarantees of privacy that must be fulfilled effectively. Often the bank neglects the internet banking security system. The purpose of this study was to determine how the perception of IAIN Padangsidmpuan students about the security of internet banking services. The theories used in this research are the theories put forward by Bimo Walgito which discusses the notion of perception, various perceptions, factors that influence perception, the characteristics of perception, the process of perception, understanding of security, types of security systems. network, security indicators, basic components of a security system, understanding of internet banking, benefits of internet banking, advantages of internet banking, and security of internet banking transactions. This research uses descriptive qualitative method. The subjects of this study were students of the Islamic Economics and Business Faculty of IAIN Padangsidimpuan class of 2017 and 2018 as many as 25 informants to describe research problems regarding the Perceptions of IAIN Padangsidimpuan Students About Internet Banking Service Security in Islamic Banking Transactions with the data sources used were primary data and secondary data. The technique of collecting data is by observation, interviews and documentation. The results of this study regarding the perceptions of IAIN Padangsidimpuan students about the security of internet banking services in Islamic banking transactions, the researchers conclude that the perceptions of IAIN Padangsidimpuan students about internet banking services are very good where internet banking services are one of the banking services that allow customers to make transactions via the internet network. . Because this service will really help students in making transactions such as checking balances, transferring money, paying tuition fees, buying credit vouchers and buying electricity tokens.